A combined strip theory and smoothed particle hydrodynamics approach for estimating slamming loads on a ship in head seas - Veen, Daniel; Gourlay, Tim (Elsevier, 2012)
Smoothed Particle Hydrodynamics (SPH) is a mesh-free Lagrangian numerical method suited to modelling fluids with a freely deforming surface. A two-dimensional SPH algorithm has been developed and applied to the problem of ship keel and bow-flare slamming. Freely decelerating drop tests of a model flared hull section were used as a basis for an initial validation of the SPH model. Relative vertical velocity profiles measured during tow tank experiments were then imposed on two-dimensional SPH models and reasonable agreement between the experimental and numerical slamming pressures was found. Finally, relative vertical velocity profiles calculated using SEAWAY software were implemented in the SPH algorithm, so as to simulate slamming on a typical V-form hull model.